2016
DOI: 10.1038/srep38007
|View full text |Cite
|
Sign up to set email alerts
|

Surface Protonics Promotes Catalysis

Abstract: Catalytic steam reforming of methane for hydrogen production proceeds even at 473 K over 1 wt% Pd/CeO2 catalyst in an electric field, thanks to the surface protonics. Kinetic analyses demonstrated the synergetic effect between catalytic reaction and electric field, revealing strengthened water pressure dependence of the reaction rate when applying an electric field, with one-third the apparent activation energy at the lower reaction temperature range. Operando–IR measurements revealed that proton conduction vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 33 publications
4
88
0
Order By: Relevance
“…To assess kinetic changes by the imposing the electric field from the viewpoint of surface adsorbate, we conducted investigations using operando ‐diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) measurements. As depicted in Figure , the peak assigned to rotation of adsorbed water (855 cm −1 ) was observed only when the electric field was imposed to M/CeO 2 catalysts with methane and water at a low temperature: 473 K . This peak is regarded as having a strong relation with the Grotthuss mechanism, a widely known mechanism of proton conduction.…”
Section: Electro‐catalytic Reactionmentioning
confidence: 93%
See 1 more Smart Citation
“…To assess kinetic changes by the imposing the electric field from the viewpoint of surface adsorbate, we conducted investigations using operando ‐diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) measurements. As depicted in Figure , the peak assigned to rotation of adsorbed water (855 cm −1 ) was observed only when the electric field was imposed to M/CeO 2 catalysts with methane and water at a low temperature: 473 K . This peak is regarded as having a strong relation with the Grotthuss mechanism, a widely known mechanism of proton conduction.…”
Section: Electro‐catalytic Reactionmentioning
confidence: 93%
“… Operando –DRIFTS spectra in the O–H rotation region over CeO 2 or 1wt%Pd/CeO 2 with and without an electric field (5 mA): flow, CH 4 :H 2 O:Ar=1:2:62; total 65 SCCM.…”
Section: Electro‐catalytic Reactionmentioning
confidence: 99%
“…Our earlier studies [12][13][14][15][16][17][18][19] revealed that application of an electric eld (EF) to Pd, Pt, or Rh catalyst supported on CeO 2 enabled MSR to proceed even at low temperature such as 473 K. Especially in a lower temperature region (T < 600 K), CH 4 conversion exceeded the thermodynamic equilibrium. 15 Furthermore, various experiments were conducted to investigate the reaction mechanism with EF, and the following results were obtained. Firstly, to observe changes of the surface species with EF, operandodiffuse reectance infrared Fourier transform (DRIFT) measurements using Pd/CeO 2 catalyst were conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, to observe changes of the surface species with EF, operandodiffuse reectance infrared Fourier transform (DRIFT) measurements using Pd/CeO 2 catalyst were conducted. 15 When EF was applied, the peak at 855 cm À1 was observed, which strongly relates to proton conduction via H bond of water, so-called the Grotthuss mechanism. Furthermore, peak of the O-H stretching bond shied to lower wavenumber, which indicated that the water is activated by applying EF.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, imposing the electric field to the catalyst bed enabled proceeding of the low temperature reaction at the temperatures of the exhaust gas (473-673 K). From the results of operando-diffuse reflectance infrared Fourier transform spectroscopy (operando-DRIFTS), proton hopping via adsorbed water on the catalyst surface occurred with the electric field, known as the Grotthuss mechanism, and the surface protonics by the application of electric field served an important role in the enhancement of SRM 35) . Referring these results, this mechanism would be applied to TRM because of the existence of H2O as a reactant gas.…”
Section: Effects Of the Electric Field And Temperaturementioning
confidence: 99%